Design, synthesis, and biological evaluation of urea‐based ROCK2 inhibitors. (5th October 2021) - Wang, Linan; Qi, Junhui; Fan, Meixia; Yao, Lei
Abstract: A series of urea‐based ROCK2 inhibitors were design and synthesized. The inhibitory activity on ROCK2 was screened by enzyme‐linked immunosorbent assay (ELISA). The study results showed that the urea derivatives exhibited certain ROCK2 inhibitory activity. The most potent compound 10p showed ROCK2 inhibitory activity with the IC50 value of 0.03 μM. A preliminary structure‐activity relationship was then summarized. The molecular docking studies showed that further optimization needs to conduct to obtain more potent ROCK inhibitors. Abstract : A series of urea‐based ROCK2 inhibitors were design and synthesized, and their ROCK 2 inhibitory activities were screened by enzyme‐linked immunosorbent assay (ELISA). Compound 10p showed the most inhibitory activity with the IC50 value of 0.03 μM.